6-Bromoindirubin-3′oxime (BIO) decreases proliferation and migration of canine melanoma cell lines. Issue 2 (August 2015) - Chon, Esther; Flanagan, Brandi; de Sá Rodrigues, Lucas Campos; Piskun, Caroline; Stein, Timothy J.
Abstract Despite recent therapeutic advances, malignant melanoma is an aggressive tumor in dogs and is associated with a poor outcome. Novel, targeted agents are necessary to improve survival. In this study, 6-bromoindirubin-3′-oxime (BIO), a serine/threonine kinase inhibitor with reported specificity for glycogen synthase kinase-3 beta (GSK-3β) inhibition, was evaluated in vitro in three canine melanoma cell lines (CML-10C2, UCDK9M2, and UCDK9M3) for β-catenin-mediated transcriptional activity, Axin2 gene and protein expression levels, cell proliferation, chemotoxicity, migration and invasion assays. BIO treatment of canine malignant melanoma cell lines at 5 µM for 72 h enhanced β-catenin-mediated transcriptional activity, suggesting GSK-3β inhibition, and reduced cell proliferation and migration. There were no significant effects on invasion, chemotoxicity, or apoptosis. The results suggest that serine/threonine kinases may be viable therapeutic targets for the treatment of canine malignant melanoma.